Littlecote Manor
Since peaceful days were known during the period, the English manor no longer needed to serve as a bastion. The houses were now build on arable, cultivated land, and a considerable subsistence was derived from the soil. The master of the household, with his new influence in government, attended court or carried out his trade in the city but his country home was built for his comfort and relaxation. Littlecote was completed in 1590 by Sir John Popham, Lord Chief Justice of England.